“Struggle Work”:: Global and Urban Citizenship in Dionne Brand’s What We All Long For - Dobson, Kit (Studies in Canadian Literature)

(untitled) (The University of New Brunswick, 2006)
Dionne Brand's 2005 novel What We All Long For represents a generational shift in the politics of being in Canadian space. In it, young, poor, and racialized characters navigate their lives and loves within the urban space of the Greater Toronto Area. Instead of pledging allegiance to the nation-state or longing for a lost home, drifting between or beyond such positions makes possible a new and liberating politics. Brand pursues a rhizomatic form of political resistance in her writing, in which one point can connect to any other to form communities. Old notions of grounded selfhood and belonging are necessarily disrupted in order to uncover a site for being that is open, neither nostalgic nor caught within the politics of inclusion/exclusion or an inside/outside dichotomy. Brand's deterritorializing project is importantly focused upon urban modes of being that constantly elude the dominant. The novel demonstrates this point in focusing upon protagonists who work actively to construct a new Toronto from below, but whose relatives and friends are caught within a racist system that seeks to limit how their bodies and beings might function.